Marguerite de Navarre - Butterworth, Emily (Gallica Ser., 2022)
A new exploration of the complexities and resolutions at play in the writings of Marguerite de Navarre, offering insights into how her work reflected the turbulence, uncertainties, and assurances of her historical period.